Relations between immigration and adult skills: Findings based on PIAAC - Patrik Lind; Erik Mellander (Institute for Evaluation of Labour Market and Education Policy (IFAU), 2016)
The international survey of adult skills, PIAAC, records large differences in numeracy and literacy skills between immigrants and non-immigrants. We examine how these differences relate to the countries' average skills and skill rankings. Immigrants are defined by country of birth or in terms of languages spoken. For almost all countries, the differences in average skills between non-immigrants and the country's entire population are significant but small. Regarding skill rankings significant differences are found only for Sweden and these are found to be sensitive to the treatment of individuals that could not conduct the skill tests due to language difficulties.
Keywords: I24; J15; O15; C15; 330; PIAAC; migration; language skills; average scores; rank uncertainty